1981
DOI: 10.3171/jns.1981.55.3.0364
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-stimulated astroglial swelling in cat cerebral cortex in vivo with total inhibition by a non-diuretic acylaryloxyacid derivative

Abstract: The intact cerebral cortices of cats were exposed in vivo under normothermic conditions and superfused with isotonic artificial cerebrospinal fluid containing added 0.125 mM adenosine. This resulted in chloridecation-rich cerebrocortical swelling which was shown by electron microscopy to be associated with an expanded astroglial compartment. The addition of DCPIB, a non-diuretic acylaryloxyacid analogue of ethacrynic acid and an inhibitor of coupled chloride-cation transport in cerebral cortex in vitro, totall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…DCPIB displays minimal inhibition of other Cl − and K + currents (< 10% inhibition at 10 µM), and inhibits glucose-stimulated insulin secretion in intact β-cells via VRAC inhibition and indirect K ATP channel activation. It reverses cell swelling-induced action potential duration shortening in atrial myocytes and inhibits astroglial swelling in vitro (Abdullaev et al, 2006;Bourke et al, 1981;Best et al, 2004). DCPIB has been shown to be a specific antagonist of volume regulated anion channels (VRAC) using cell expression systems where it was shown not to have any effect on a variety of expressed Cl − channels , but to be a very effective inhibitor of VRAC activity in swollen cells (Decher et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DCPIB displays minimal inhibition of other Cl − and K + currents (< 10% inhibition at 10 µM), and inhibits glucose-stimulated insulin secretion in intact β-cells via VRAC inhibition and indirect K ATP channel activation. It reverses cell swelling-induced action potential duration shortening in atrial myocytes and inhibits astroglial swelling in vitro (Abdullaev et al, 2006;Bourke et al, 1981;Best et al, 2004). DCPIB has been shown to be a specific antagonist of volume regulated anion channels (VRAC) using cell expression systems where it was shown not to have any effect on a variety of expressed Cl − channels , but to be a very effective inhibitor of VRAC activity in swollen cells (Decher et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of these compounds was guided by the principle of increasing their efficacy in inhibiting brain edema and reducing their renal saludiuretic effects (Nelson et al, 1979;Kimelberg et al, 1987;Kimelberg et al, 1990;Bourke et al, 1979;Cragoe et al, 1982;Cragoe, Jr. et al, 1986;Cragoe, 1987). Since that time one of these compounds 4-(2-butyl-6,7-dichloro-2-cyclopentyl-indan-1-on-5-yl) oxobutyric acid and therefore given the acronym DCPIB Bourke et al, 1981;Nelson et al, 1982); and see Figure 1a), has been shown to specifically inhibit VRAC activity, but not a number of expressed chloride channels in Xenopus oocytes (Decher et al, 2001). VRACs are an important class of anion channels that are widely distributed, but whose molecular identity has so far eluded investigators' best efforts (Nilius and Droogmans, 2003;Strange, 1998;Okada, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…To verify the specificity of DCPIB action we analysed the effect of ethacrynic acid (EA), the molecule from which DCPIB is derived (Bourke et al, 1981;Cragoe et al, 1982). In COS-7 cells transfected with K2P 2.1 and K2P 10.1 that responded to DCPIB (10 mM) application of 30 mM EA did not cause any increase in membrane conductance ( Figure 5C, D).…”
Section: Figurementioning
confidence: 99%
“…One of the best characterized agent that modulates these processes is the ethacrynic acid derivative, 4-(2-butyl-6,7-dichlor-2-cyclopentylindan-1-on-5-yl) oxobutyric acid (DCPIB). DCPIB was reported to block totally astroglial swelling induced in cat cerebral cortex (Bourke et al, 1981). In adult rats, DCPIB caused a reduction in size of infarct volume when applied intracisternally during 2 h of middle cerebral artery occlusion (MCAO), and decreased MCAO-induced glutamate release in the penumbra (Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in taurine release by adenosine may occur to compensate the osmotic imbalance triggered by adenosine-induced astroglial swelling via cAMP accumulation (Bourke et al, 1981). It is not clear why and how adenosine causes astroglial swelling.…”
mentioning
confidence: 99%